The Application of Coconut Water at Various Levels of Robustness for Improving The Physiological Quality of Onion True Shallot Seed - Retno Dwi Andayani (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
Shallots are one of vegetable that can be cultivated with bulb or seeds. Shallot seeds better known as True Shallot Seed (TSS). Shallot cultivation using TSS still encounters several obstacles including low physiological quality of seeds. Physiological quality of seeds can be improved by plant growth regulators (PGR) application both natural or artificial. One of popular natural PGR is coconut water. The goal of this experiment was to determinate the effectiveness of various types of coconut water at freshness various levels toimprove TSS physiological quality. This experiment use factorial completely randomized design with 3 replications. First factor is 3 types of coconut water that are Gading Coconut, Hijau Coconut and Dalam Coconut. Second factor is 4 levels of water coconut freshness that are fresh coconut water, coconut water stored for 1 day, coconut water strored for 2 days and coconut water stored for 3 days. TSS used in this experient was Tisula variety. The result showed that various types of coconut water could improve physiological quality of TSS. Maksimum results obtained in HijauCoconut water with fresh, stored 1 day and strored 2 days treatment. Also Dalam Coconut water in fresh and stored 1 day. Gading Coconut water is also able to improve TSS physiological quality although the result as not as good Hijau Coconut and Dalam Coconut.